Differences in the Faecal Microbiome in Schistosoma haematobium Infected Children vs. Uninfected Children - Kay, Gemma Louise; Millard, Andrew; Sergeant, Martin J.; Midzi, Nicholas; Gwisai, Reggis; Mduluza, Takafira; Ivens, Alasdair; Nausch, Norman; Mutapi, Francisca; Pallen, Mark (PLoS neglected tropical diseases, 2015)
Several infectious diseases and therapeutic interventions cause gut microbe dysbiosis and associated pathology. We characterised the gut microbiome of children exposed to the helminth Schistosoma haematobium pre- and post-treatment with the drug praziquantel (PZQ), with the aim to compare the gut microbiome structure (abundance and diversity) in schistosome infected vs. uninfected children. Stool DNA from 139 children aged six months to 13 years old; with S. haematobium infection prevalence of 27.34% was extracted at baseline. 12 weeks following antihelminthic treatment with praziqunatel, stool DNA was collected from 62 of the 139 children. The 16S rRNA genes were sequenced from the baseline and post-treatment samples and the sequence data, clustered into operational taxonomic units (OTUs). The OTU data were analysed using multivariate analyses and paired T-test. Pre-treatment, the most abundant phyla were Bacteroidetes, followed by Firmicutes and Proteobacteria respectively. The relative abundance of taxa among bacterial classes showed limited variation by age group or sex and the bacterial communities had similar overall compositions. Although there were no overall differences in the microbiome structure across the whole age range, the abundance of 21 OTUs varied significantly with age (FDR<0.05). Some OTUs including Veillonella, Streptococcus, Bacteroides and Helicobacter were more abundant in children ≤ 1 year old compared to older children. Furthermore, the gut microbiome differed in schistosome infected vs. uninfected children with 27 OTU occurring in infected but not uninfected children, for 5 of these all Prevotella, the difference was statistically significant (p <0.05) with FDR <0.05. PZQ treatment did not alter the microbiome structure in infected or uninfected children from that observed at baseline. There are significant differences in the gut microbiome structure of infected vs. uninfected children and the differences were refractory to PZQ treatment.